Thermally conductive two-pack addition curable type silicon composition
Patent Information
- Application Number
- JP2023124946
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-13
- Estimated Expiration
- 2043-07-31
AI Technical Summary
【0017】 以上のように、本発明の熱伝導性シリコーン組成物は、組成物の加熱硬化中および硬化後に、オイルブリードすることなく、放熱性に優れる。
Smart Images

Figure 2025021180000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermally conductive two-part addition-curable silicone composition. [Background technology]
[0002] In recent years, with the high integration and high voltage of electronic component circuits, the amount of heat generated from ICs and circuits has increased, so silicone compositions with good thermal conductivity are used as heat dissipation materials.It is known that in order to improve thermal conductivity, it is sufficient to use a thermally conductive filler in the above composition, and known examples of such fillers include silica powder, aluminum oxide powder, silicon carbide powder, silicon nitride powder, aluminum nitride powder, magnesium oxide powder, diamond powder, metal powder such as iron, stainless steel, and copper, as well as carbon powder.
[0003] Various compositions containing these fillers have been proposed. Among them, methods for producing silicone compositions using aluminum oxide powder as a filler have been proposed so far because of its good thermal conductivity, electrical insulation, workability, etc. (Patent Documents 1 to 3). For example, aluminum oxide powder was extracted by heating in pure water at 120°C for 48 hours, and the aqueous layer was measured by ion chromatography to find that the Na content was 1.0 g / g. + It is known that the shelf life can be improved and changes in hardness over time can be suppressed by using a composition that is a mixture of aluminum oxide having an ion amount of 100 ppm or less, an oil component such as an organopolysiloxane, and, as necessary, a cation exchange and / or amphoteric ion exchange type ion trapping agent that promotes improvement of the shelf life of the composition (Patent Document 4).
[0004] However, the above-mentioned thermally conductive silicone compositions contain, in addition to oil components such as organopolysiloxane that are incorporated in the reaction with the thermally conductive filler, free oil components that are not incorporated in the reaction in order to impart effects such as a lower elastic modulus of the composition and improved workability during application, and therefore the composition may suffer from oil bleeding during or after curing, and this may worsen over time, causing problems such as contamination of surrounding parts such as electric and electronic components and deterioration of thermal performance. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 2741436 [Patent Document 2] Patent No. 3676544 [Patent Document 3] Patent No. 5821160 [Patent Document 4] Patent Publication No. 2022-29985 Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention has been made in order to solve the above problems, and has an object to provide a thermally conductive two-component addition-curable silicone composition which has a sufficient time until the composition begins to cure, and which can significantly reduce oil bleeding during and after curing of the composition. [Means for solving the problem]
[0007] In order to solve the above problems, the present invention provides a thermally conductive two-part addition-curable silicone composition, comprising: (A) The following average composition formula (1) R a R 1 b SiO (4-a-b) / 2 (1) (wherein R is independently an alkenyl group; R 1are independently an unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bond, a is 0.0001 to 0.2, b is 1.7 to 2.2, and a+b is a positive number satisfying 1.9 to 2.4. and having at least two alkenyl groups bonded to silicon atoms in one molecule, (C) Aluminum oxide powder was heated and extracted with pure water at 120℃ for 48 hours, and the aqueous layer was measured for Na by ion chromatography. + Aluminum oxide powder with an ionic content of 100 ppm or less, and (E) Platinum group metal catalyst: 1 to 200 ppm by mass of platinum group metal relative to component (A) A first liquid containing (A) The following average composition formula (1) R a R 1 b SiO (4-a-b) / 2 (1) (wherein R is independently an alkenyl group; R 1 are independently an unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bond, a is 0.0001 to 0.2, b is 1.7 to 2.2, and a+b is a positive number satisfying 1.9 to 2.4. and having at least two alkenyl groups bonded to silicon atoms in one molecule, (B) The following average composition formula (2) R 2 c H d SiO (4-c-d) / 2 (2) (In the formula, R 2 are independently an unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bond, c is 0.7 to 2.2, d is 0.001 to 0.5, and c+d is a positive number that satisfies 0.8 to 2.5. an organohydrogenpolysiloxane having at least three hydrogen atoms bonded to silicon atoms in one molecule, wherein the number of silicon-bonded hydrogen atoms (SiH groups) in component (B) is 0.1 to 2 per alkenyl group in component (A); (C) Aluminum oxide powder was heated and extracted with pure water at 120℃ for 48 hours, and the aqueous layer was measured for Na by ion chromatography. + Aluminum oxide powder with an ion content of 100 ppm or less, (D) The average composition formula (3) below R 3 e H f SiO (4-e-f) / 2 (3) (In the formula, R 3 are independently an unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bonds, e is a positive number that satisfies 0.7 to 2.2, f is a positive number that satisfies 0.001 to 0.5, and e+f is a positive number that satisfies 0.8 to 2.5. an organohydrogenpolysiloxane different from component (B) having two hydrogen atoms bonded to silicon atoms in one molecule: component (D) in an amount such that there are 0.01 to 3 silicon-bonded hydrogen atoms (SiH groups) per alkenyl group in component (A), and (F) Reaction control agent: A reaction control agent having 1 to 4 alkenyl groups in one molecule and a D unit (R 4 2SiO 2 / 2 )(R 4 are independently unsubstituted or substituted monovalent hydrocarbon groups that do not have aliphatic unsaturated bonds. and a second liquid comprising the composition, provided is a thermally conductive two-part addition curable silicone composition, characterized in that the first part does not contain the components (B), (D), or (F), the second part does not contain the component (E), the total amount of the component (A) in the composition is 100 parts by mass, the total amount of the component (C) is 1,000 to 7,000 parts by mass, and the amount of the component (F) is 0.01 to 1 part by mass, the first part and the second part each have a thermal conductivity of 2.0 to 7.0 W / m K when measured using a hot disk method in accordance with ISO 22007-2, and the first part and the second part each have a viscosity at 25°C of 30 to 800 Pa s when measured using a spiral viscometer with rotor A at a rotation speed of 10 rpm (shear rate of 6 (1 / sec)).
[0008] With the thermally conductive two-part addition cure silicone composition of the present invention, there is sufficient time before the composition begins to cure, making it possible to significantly reduce oil bleeding during and after curing of the composition.
[0009] In this case, it is preferable that the ratio of the total number of SiH groups in the components (B) and (D) to the number of alkenyl groups in the component (A) is 0.11 to 5.
[0010] So long as the combined total amount of SiH groups in components (B) and (D) is within the above range, a stable silicone cured product with appropriate softness can be obtained, and the resulting silicone cured product will also have favorable hardness and strength.
[0011] In addition, the present invention further comprises a silane coupling agent (G) and / or a compound represented by the following general formula (4): [ka] (In the formula, R 4 are independently unsubstituted or substituted monovalent hydrocarbon groups; R 5 are independently an alkyl group, an alkoxyalkyl group, an alkenyl group or an acyl group, g is an integer of 5 to 100, and h is an integer of 1 to 3. It is preferable that the first liquid and / or the second liquid contain an organopolysiloxane (H) having a viscosity at 25° C. of 0.01 to 30 Pa·s.
[0012] With such a thermally conductive two-part addition curable silicone composition, the first and second parts can be made low viscosities.
[0013] In the present invention, when the first liquid and the second liquid are mixed in a mass ratio of 1:1 and a tack-free test is carried out at 25°C in accordance with JIS K6249, it is preferable that the tack-free time is 30 minutes or more and 200 minutes or less.
[0014] When the tack-free time is within the above range, the curing start time of the composition is appropriate, workability is good, and there is no risk of contamination of surrounding members due to oil bleeding or deterioration of thermal performance.
[0015] In the present invention, when a mixture obtained by mixing the first liquid and the second liquid in a mass ratio of 1:1 is applied to a ground glass having a surface roughness of 3 to 20 μm in arithmetic mean height and 10 to 100 μm in maximum height as specified in ISO 25178, in an amount of 0.1 g to a diameter of 3 to 5 mm, it is preferable that (i) after being left at 25° C. for 24 hours, the width of oil bleed around the mixture is 1.0 mm or less, (ii) after being left at 150° C. for 500 hours, the width of oil bleed around the mixture is 1.0 mm or less, or (iii) after being left at 85° C. and a humidity of 85% for 500 hours, the width of oil bleed around the mixture is 1.0 mm or less.
[0016] Such a composition of the present invention is preferable because it suppresses oil bleeding and therefore there is no risk of contamination of surrounding members or deterioration of thermal performance. Effect of the Invention
[0017] As described above, the thermally conductive silicone composition of the present invention exhibits excellent heat dissipation properties and does not exhibit oil bleeding during or after the composition is cured by heating. [Brief description of the drawings]
[0018] [Figure 1] FIG. 2 is a schematic diagram showing an oil-bleed measuring method in an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] As described above, there has been a demand for the development of an addition-curing silicone composition that can solve the problems of oil bleeding during or after the composition is cured, which deteriorates over time and leads to contamination of surrounding parts such as electric and electronic components and deterioration of thermal performance.
[0020] Means for Solving the Problems The present inventors have conducted extensive research into the above-mentioned problems and have discovered that by skillfully combining and adjusting the structure and amount of an organopolysiloxane that has the effect of controlling a hydrosilylation reaction, and the amount of a platinum group metal catalyst (hydrosilylation catalyst), it is possible to ensure that there is sufficient time until the composition begins to cure, and to significantly suppress oil bleeding after the composition begins to cure, thereby completing the present invention.
[0021] That is, the present invention provides a thermally conductive two-part addition-curable silicone composition, (A) The following average composition formula (1) R a R 1 b SiO (4-a-b) / 2 (1) (wherein R is independently an alkenyl group; R 1 are independently an unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bond, a is 0.0001 to 0.2, b is 1.7 to 2.2, and a+b is a positive number satisfying 1.9 to 2.4. and having at least two alkenyl groups bonded to silicon atoms in one molecule, (C) Aluminum oxide powder was heated and extracted with pure water at 120℃ for 48 hours, and the aqueous layer was measured for Na by ion chromatography. + Aluminum oxide powder with an ionic content of 100 ppm or less, and (E) Platinum group metal catalyst: 1 to 200 ppm by mass of platinum group metal relative to component (A) A first liquid containing (A) The following average composition formula (1) R a R 1 b SiO (4-a-b) / 2 (1) (wherein R is independently an alkenyl group; R 1 are independently an unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bond, a is 0.0001 to 0.2, b is 1.7 to 2.2, and a+b is a positive number satisfying 1.9 to 2.4. and having at least two alkenyl groups bonded to silicon atoms in one molecule, (B) The following average composition formula (2) R 2 c H d SiO (4-c-d) / 2 (2) (In the formula, R 2 are independently an unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bond, c is 0.7 to 2.2, d is 0.001 to 0.5, and c+d is a positive number that satisfies 0.8 to 2.5. an organohydrogenpolysiloxane having at least three hydrogen atoms bonded to silicon atoms in one molecule, wherein the number of silicon-bonded hydrogen atoms (SiH groups) in component (B) is 0.1 to 2 per alkenyl group in component (A); (C) Aluminum oxide powder was heated and extracted with pure water at 120℃ for 48 hours, and the aqueous layer was measured for Na by ion chromatography. + Aluminum oxide powder with an ion content of 100 ppm or less, (D) The average composition formula (3) below R 3 e H f SiO (4-e-f) / 2 (3) (In the formula, R 3 are independently an unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bonds, e is a positive number that satisfies 0.7 to 2.2, f is a positive number that satisfies 0.001 to 0.5, and e+f is a positive number that satisfies 0.8 to 2.5. an organohydrogenpolysiloxane different from component (B) having two hydrogen atoms bonded to silicon atoms in one molecule: component (D) in an amount such that there are 0.01 to 3 silicon-bonded hydrogen atoms (SiH groups) per alkenyl group in component (A), and (F) Reaction control agent: A reaction control agent having 1 to 4 alkenyl groups in one molecule and a D unit (R 4 2SiO 2 / 2 )(R 4 are independently unsubstituted or substituted monovalent hydrocarbon groups that do not have aliphatic unsaturated bonds. and a second liquid comprising the composition, the first liquid does not contain the components (B), (D), or (F), the second liquid does not contain the component (E), the total amount of the component (A) in the composition is 100 parts by mass, the total amount of the component (C) is 1,000 to 7,000 parts by mass, and the amount of the component (F) is 0.01 to 1 part by mass, the first liquid and the second liquid each have a thermal conductivity of 2.0 to 7.0 W / m K when measured using a hot disk method in accordance with ISO 22007-2, and the first liquid and the second liquid each have a viscosity at 25°C of 30 to 800 Pa s when measured using a spiral viscometer with rotor A at a rotation speed of 10 rpm (shear rate of 6 (1 / sec)).
[0022] The present invention will be described in detail below, but the present invention is not limited thereto.
[0023] [Thermal conductive two-part addition curing silicone composition] The present invention relates to a thermally conductive two-part addition-curable silicone composition that has excellent thermal conductivity and does not cause oil-bleeding. The thermally conductive two-component addition-curable silicone composition of the present invention comprises (A) an organopolysiloxane having two or more specific alkenyl groups, (C) an extracted Na + The composition comprises a first liquid containing aluminum oxide powder in an amount of 100 ppm or less and (E) a platinum group metal catalyst, and a second liquid containing the component (A), (B) an organohydrogenpolysiloxane having three or more SiH groups, the component (C), (D) an organohydrogenpolysiloxane having two SiH groups different from the component (B), and (F) a reaction inhibitor. However, the first liquid does not contain the components (B), (D), or (F), and the second liquid does not contain the component (E). The composition is characterized in that the first liquid and the second liquid each have a thermal conductivity of 2.0 to 7.0 W / m·K and a viscosity at 25°C of 30 to 800 Pa·s. If necessary, the composition may contain other components than those listed above. The components constituting the composition of the present invention will be described below.
[0024] [Component (A)] The component (A) of the composition of the present invention is a component that serves as the main component (base polymer) of the composition. The component (A) is an organopolysiloxane represented by the following average composition formula (1) and having at least two alkenyl groups bonded to silicon atoms (hereinafter referred to as "silicon-bonded alkenyl groups") in one molecule. At least two silicon-bonded alkenyl groups are present in one molecule, preferably 2 to 50, and more preferably 2 to 20. These silicon-bonded alkenyl groups may be bonded to silicon atoms at the molecular chain terminals, or to silicon atoms at non-terminal locations (i.e., other than the molecular chain terminals), or a combination thereof. R a R 1 b SiO (4-a-b) / 2 (1) (wherein R is independently an alkenyl group; R 1 are independently an unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bond, a is 0.0001 to 0.2, b is 1.7 to 2.2, and a+b is a positive number satisfying 1.9 to 2.4.
[0025] In the above formula (1), R is usually an alkenyl group having 2 to 6 carbon atoms, preferably 2 to 4. Specific examples thereof include lower alkenyl groups such as a vinyl group, an allyl group, a propenyl group, an isopropenyl group, a butenyl group, and an isobutenyl group, with a vinyl group being particularly preferred.
[0026] R 1is usually an unsubstituted or substituted monovalent hydrocarbon group having 1 to 10 carbon atoms, preferably 1 to 6 carbon atoms, and having no aliphatic unsaturated bonds. Specific examples thereof include alkyl groups such as methyl, ethyl, propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, pentyl, hexyl, cyclohexyl, octyl, and decyl; aryl groups such as phenyl and tolyl; aralkyl groups such as benzyl and phenylethyl; and chloromethyl and 3,3,3-trifluoropropyl groups in which some or all of the hydrogen atoms of these groups are substituted with halogen atoms such as fluorine, chlorine, and bromine. From the viewpoint of ease of synthesis, etc., a methyl group, a phenyl group, and a 3,3,3-trifluoropropyl group are preferred.
[0027] Furthermore, a is a positive number of 0.0001 to 0.2, and preferably a positive number of 0.0005 to 0.1, b is a positive number of 1.7 to 2.2, and preferably a positive number of 1.9 to 2.0, and a+b is a positive number satisfying 1.9 to 2.4, and preferably a positive number satisfying 1.95 to 2.05.
[0028] The molecular structure of the organopolysiloxane of component (A) is not particularly limited, and may be linear; 3 / 2 Units, R 1 SiO 3 / 2 unit, SiO unit (wherein R and R 1 The group represented by the formula (I) is as defined above), and may be any of branched chain, cyclic, three-dimensional network (resinous), and combinations thereof. However, linear diorganopolysiloxanes in which the main chain is basically composed of repeating diorganosiloxane units and both molecular chain terminals are blocked with triorganosiloxy groups are particularly preferred.
[0029] The viscosity of the organopolysiloxane of component (A) is preferably 50 to 100,000 mPa·s, and more preferably 100 to 10,000 mPa·s. When the viscosity is 50 to 100,000 mPa·s, the resulting cured product has better strength, fluidity, and workability. The viscosity is a value measured at 25°C using a rotational viscometer (spiral viscometer) (hereinafter the same).
[0030] Examples of organopolysiloxanes of component (A) that satisfy the above requirements include those represented by the following general formula (1A): [ka] (In the formula, R 6 are independently unsubstituted or substituted monovalent hydrocarbon groups, where R 6 At least two of the groups are alkenyl groups, and i is an integer of 20 to 2,000. Examples of the above-mentioned are represented by the following formula:
[0031] In this formula (1A), R 6 The unsubstituted or substituted monovalent hydrocarbon group represented by the formula (I) is the same as the R (alkenyl group) and R 1 (Unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bonds), and the number of carbon atoms, specific examples, etc. are also the same. However, R 6 At least two of the i's are alkenyl groups, preferably 2 to 50, and more preferably 2 to 20. Also, i's is an integer of 20 to 2,000, preferably 40 to 1,200, and more preferably 50 to 600.
[0032] Specific examples of organopolysiloxanes represented by the above formula (1A) include dimethylpolysiloxanes capped at both molecular chain terminals with dimethylvinylsiloxy groups, dimethylsiloxane-methylvinylsiloxane copolymers capped at both molecular chain terminals with trimethylsiloxy groups, dimethylsiloxane-methylvinylsiloxane copolymers capped at one molecular chain terminal with a trimethylsiloxy group and one terminal with a dimethylvinylsiloxy group, dimethylsiloxane-methylvinylsiloxane copolymers capped at both molecular chain terminals with dimethylvinylsiloxy groups, and dimethylsiloxane-diphenylsiloxane copolymers capped at both molecular chain terminals with dimethylvinylsiloxy groups.
[0033] The organopolysiloxane of the component (A) may use either a single compound, or a combination of two or more different compounds.
[0034] The above-mentioned organopolysiloxanes having alkenyl groups are themselves known and can be produced by conventional methods.
[0035] The (A) component is used in both the first liquid and the second liquid, and the ratio of the (A) component used in the first liquid and the second liquid is not particularly limited as long as it can be used so that the mixing ratio of the first liquid to the second liquid is approximately the same mass ratio.
[0036] [(B) Component] Component (B) of the composition of the present invention has at least three hydrogen atoms bonded to silicon atoms in one molecule, and acts as a surface treatment agent and crosslinking agent for aluminum oxide, component (C). That is, when heat-treated at high temperature, a portion of it is consumed by a dehydrogenation reaction with Al-OH groups remaining on the surface of component (C) and with the inorganic acid surface treatment agent residue, and the remaining hydrogen atoms bonded to silicon atoms undergo an addition reaction with alkenyl groups in component (A), and is an essential component of the present invention.
[0037] The component (B) is an organohydrogenpolysiloxane represented by the following average composition formula (2) and having at least three hydrogen atoms bonded to silicon atoms (hereinafter also referred to as "silicon-bonded hydrogen atoms") in one molecule. The number of silicon-bonded hydrogen atoms in one molecule of this organohydrogenpolysiloxane is preferably 3 to 100, more preferably 3 to 50, and particularly preferably 3 to 20. The hydrogen atoms bonded to silicon atoms may be located at the molecular chain terminals, in the middle of the molecular chain, or both. R 2 c H d SiO (4-c-d) / 2 (2) (In the formula, R 2 are independently an unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bond, c is 0.7 to 2.2, d is 0.001 to 0.5, and c+d is a positive number that satisfies 0.8 to 2.5.
[0038] In the above formula (2), R 2 are independently unsubstituted or substituted monovalent hydrocarbon groups having no aliphatic unsaturated bonds, and the number of carbon atoms is usually 1 to 10, preferably 1 to 6. Specific examples thereof include alkyl groups such as methyl, ethyl, propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, cyclohexyl, octyl, nonyl, and decyl; aryl groups such as phenyl, tolyl, xylyl, and naphthyl; aralkyl groups such as benzyl, phenylethyl, and phenylpropyl; and 3,3,3-trifluoropropyl groups in which some or all of the hydrogen atoms of these groups are substituted with halogen atoms such as fluorine, chlorine, and bromine. Among these, alkyl groups, aryl groups, and 3,3,3-trifluoropropyl groups are preferred, and methyl, phenyl, and 3,3,3-trifluoropropyl groups are more preferred.
[0039] Furthermore, c is a positive number of 0.7 to 2.2, and preferably a positive number of 1.0 to 2.1. d is a positive number of 0.001 to 0.5, and preferably a positive number of 0.005 to 0.1. c+d is a positive number satisfying 0.8 to 2.5, and preferably a positive number satisfying 1.0 to 2.5, and more preferably a positive number satisfying 1.5 to 2.2.
[0040] The number of silicon atoms in one molecule of the organohydrogenpolysiloxane of component (B) (i.e., the degree of polymerization) is typically 10 to 1,000, but from the viewpoints of improving the handling workability of the composition and the properties of the resulting cured product, it is preferably 20 to 500, and more preferably 20 to 100.
[0041] Furthermore, there are no particular limitations on the molecular structure of the organohydrogenpolysiloxane of component (B), so long as it satisfies the above requirements.
[0042] The viscosity of the organohydrogenpolysiloxane of component (B) is usually 1 to 10,000 mPa·s, preferably 3 to 2,000 mPa·s, and more preferably 10 to 1,000 mPa·s, and it is desirable for it to be liquid at room temperature (25° C.).
[0043] Examples of the organohydrogenpolysiloxane represented by the above formula (2) include methylhydrogensiloxane-dimethylsiloxane cyclic copolymers, methylhydrogenpolysiloxanes terminated at both molecular chain ends with dimethylhydrogensiloxy groups, methylhydrogen-dimethylsiloxane copolymers terminated at both molecular chain ends with dimethylhydrogensiloxy groups, methylhydrogen-diphenylsiloxane copolymers terminated at both molecular chain ends with dimethylhydrogensiloxy groups, and methylhydrogenpolysiloxanes terminated at both molecular chain ends with dimethylhydrogensiloxy groups. copolymer of methylhydrogen-dimethylsiloxane-diphenylsiloxane, methylhydrogenpolysiloxane terminated at both ends with trimethylsiloxy groups, copolymer of dimethylsiloxane-methylhydrogensiloxane terminated at both ends with trimethylsiloxy groups, copolymer of methylhydrogensiloxane-diphenylsiloxane terminated at both ends with trimethylsiloxy groups, copolymer of methylhydrogensiloxane-diphenylsiloxane-dimethylsiloxane terminated at both ends with trimethylsiloxy groups, (CH3)2HSiO 1 / 2 Units and (CH3)2SiO Units and CH3SiO 3 / 2 A copolymer consisting of the unit (CH3)2HSiO 1 / 2 Units and (C6H5)2SiO units and (CH3)2SiO units and CH3SiO 3 / 2 A copolymer consisting of the units (CH3)(C6H5)HSiO 1 / 2 Units and (CH3)2SiO Units and CH3SiO 3 / 2 A copolymer consisting of the unit (CH3)2HSiO 1 / 2 Units and (CH3)2SiO units and C6H5SiO 3 / 2 A copolymer consisting of the units (CH3)(CF3C2H4)HSiO 1 / 2 (CH3)(CF3C2H4)SiO Unit and CH3SiO 3 / 2 A copolymer consisting of the units (CH3)(CF3C2H4)HSiO 1 / 2 (CH3)(CF3C2H4)SiO unit, (CH3)2SiO unit, and CH3SiO 3 / 2 A copolymer consisting of (CH3)2HSiO units. 1 / 2 (CH3)(CF3C2H4)SiO Unit and CH3SiO 3 / 2A copolymer consisting of (CH3)2HSiO units. 1 / 2 (CH3)(CF3C2H4)SiO unit, (CH3)2SiO unit, and CH3SiO 3 / 2 A copolymer consisting of (CH3)2HSiO units. 1 / 2 Units and (CH3)(CF3C2H4)SiO Units and (CH3)2SiO Units and (CF3C2H4)SiO 3 / 2 and copolymers consisting of a unit.
[0044] The organohydrogenpolysiloxane of the component (B) may use either a single compound, or a combination of two or more different compounds.
[0045] This organohydrogenpolysiloxane is synthesized by a conventional method.
[0046] The amount of organohydrogenpolysiloxane in component (B) is such that there are 0.1 to 2 silicon-bonded hydrogen atoms (SiH groups) in component (B) per alkenyl group in component (A), preferably 0.1 to 1.8, and more preferably 0.1 to 1.5. If the amount is too small, the effect of improving storage stability may be insufficient, and if the amount is too large, the physical properties of the resulting thermally conductive silicone cured product may become unstable.
[0047] [(C) component] The component (C) of the composition of the present invention is determined by heating and extracting aluminum oxide powder in pure water at 120°C for 48 hours, and measuring the aqueous layer by ion chromatography to determine the amount of Na. + This is an aluminum oxide powder with an ion amount of 100 ppm or less.
[0048] Aluminum oxide powder was heated and extracted in pure water at 120℃ for 48 hours, and the aqueous layer was measured using ion chromatography. + Ion amount is 100ppm or less, preferably Na + The amount of Na ions is 80 ppm or less, more preferably 60 ppm or less. + If the amount of ions exceeds 100 ppm, component (E) may become inactive over time.
[0049] Here, the Na content of aluminum oxide used in the present invention is + In order to bring the amount of ions into the above range, commercially available aluminum oxide powder is dispersed in water and washed with water at room temperature (1 to 25°C) or, for example, at 60°C to shorten the process time, by stirring. + The amount of ions can be adjusted.
[0050] The aluminum oxide powder preferably has an average particle size of 1 to 100 μm, more preferably 1 to 80 μm, as measured by laser diffraction method, and the particle shape is preferably crushed particles, rounded particles, or spherical particles, and preferably crushed particles and spherical particles. If necessary, one type may be used alone, or two or more types having different average particle sizes may be used in combination. If the average particle size is 1 μm or more, there is sufficient contact between the particles, and the thermal conductivity tends to improve due to the reduction in interparticle contact thermal resistance. Also, if the average particle size is 100 μm or less, the unevenness of the sheet surface is reduced, the interface thermal resistance is reduced, and the thermal conductivity tends to improve.
[0051] The total amount of the thermally conductive filler of component (C) is 1,000 to 7,000 parts by mass, preferably 1,200 to 6,900 parts by mass, and more preferably 1,400 to 6,700 parts by mass per 100 parts by mass of component (A). When the blending amount is within the above range, it is possible to obtain a thermally conductive two-part addition curing silicone composition that gives a thermally conductive silicone cured product of the present invention that can suppress changes in viscosity, thermal conductivity, storage stability, and hardness over time. On the other hand, if the blending amount is too small, sufficient thermal conductivity cannot be ensured, and if it is too large, the viscosity increases significantly and the flowability becomes insufficient.
[0052] The (C) component is used in both the first liquid and the second liquid, and the ratio of the (C) component used in the first liquid and the second liquid is not particularly limited as long as it can be used so that the mixing ratio of the first liquid to the second liquid is approximately the same mass ratio.
[0053] [(D) component] The component (D) of the composition of the present invention is represented by the following average composition formula (3): R 3 e H f SiO (4-e-f) / 2 (3) (In the formula, R 3 are independently an unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bonds, e is a positive number that satisfies 0.7 to 2.2, f is a positive number that satisfies 0.001 to 0.5, and e+f is a positive number that satisfies 0.8 to 2.5. and, unlike component (B), is an organohydrogenpolysiloxane having two hydrogen atoms bonded to silicon atoms in each molecule.
[0054] In the above formula (3), R 3 are independently unsubstituted or substituted monovalent hydrocarbon groups having no aliphatic unsaturated bonds, and the number of carbon atoms is usually 1 to 10, preferably 1 to 6. Specific examples thereof include alkyl groups such as methyl, ethyl, propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, cyclohexyl, octyl, nonyl, and decyl; aryl groups such as phenyl, tolyl, xylyl, and naphthyl; aralkyl groups such as benzyl, phenylethyl, and phenylpropyl; and 3,3,3-trifluoropropyl groups in which some or all of the hydrogen atoms of these groups are substituted with halogen atoms such as fluorine, chlorine, and bromine. Among these, alkyl groups, aryl groups, and 3,3,3-trifluoropropyl groups are preferred, and methyl, phenyl, and 3,3,3-trifluoropropyl groups are more preferred.
[0055] Furthermore, e is a positive number of 0.7 to 2.2, and preferably a positive number of 1.0 to 2.1. f is a positive number of 0.001 to 0.5, and preferably a positive number of 0.005 to 0.1. e+f is a positive number satisfying 0.8 to 2.5, and preferably a positive number satisfying 1.0 to 2.5, and more preferably a positive number satisfying 1.5 to 2.2.
[0056] The organohydrogenpolysiloxane of component (D) has two hydrogen atoms bonded to silicon atoms per molecule. These may be located at the ends of the molecular chain, or within the molecular chain, or one on each side, but are preferably located at the ends of the molecular chain.
[0057] The number of silicon atoms in one molecule of the organohydrogenpolysiloxane of component (D) (i.e., the degree of polymerization) is typically 10 to 1,000, but from the viewpoints of improving the handling workability of the composition and the properties of the resulting cured product, it is preferably 15 to 500, and more preferably 18 to 100.
[0058] Furthermore, there are no particular limitations on the molecular structure of the organohydrogenpolysiloxane of component (D), so long as it satisfies the above requirements.
[0059] The viscosity of the organohydrogenpolysiloxane of component (D) is usually 1 to 10,000 mPa·s, preferably 3 to 2,000 mPa·s, and more preferably 10 to 1,000 mPa·s, and it is desirable for it to be in a liquid state at room temperature (25° C.).
[0060] Examples of organohydrogenpolysiloxanes represented by the above formula (3) include methylhydrogensiloxane-dimethylsiloxane cyclic copolymers, dimethylpolysiloxanes terminally blocked with dimethylhydrogensiloxy groups, methylhydrogenpolysiloxanes terminally blocked with trimethylsiloxy groups, dimethylsiloxane-methylhydrogensiloxane copolymers terminally blocked with trimethylsiloxy groups, methylhydrogensiloxane-diphenylsiloxane copolymers terminally blocked with trimethylsiloxy groups, methylhydrogensiloxane-diphenylsiloxane-dimethylsiloxane copolymers terminally blocked with trimethylsiloxy groups, (CH3)2HSiO 1 / 2 Units and (CH3)2SiO Units and CH3SiO 3 / 2 A copolymer consisting of the unit (CH3)2HSiO 1 / 2 Units and (C6H5)2SiO units and (CH3)2SiO units and CH3SiO 3 / 2A copolymer consisting of the units (CH3)(C6H5)HSiO 1 / 2 Units and (CH3)2SiO Units and CH3SiO 3 / 2 A copolymer consisting of the unit (CH3)2HSiO 1 / 2 Units and (CH3)2SiO units and C6H5SiO 3 / 2 A copolymer consisting of the units (CH3)(CF3C2H4)HSiO 1 / 2 (CH3)(CF3C2H4)SiO Unit and CH3SiO 3 / 2 A copolymer consisting of the units (CH3)(CF3C2H4)HSiO 1 / 2 (CH3)(CF3C2H4)SiO unit, (CH3)2SiO unit, and CH3SiO 3 / 2 A copolymer consisting of (CH3)2HSiO units. 1 / 2 (CH3)(CF3C2H4)SiO Unit and CH3SiO 3 / 2 A copolymer consisting of (CH3)2HSiO units. 1 / 2 (CH3)(CF3C2H4)SiO unit, (CH3)2SiO unit, and CH3SiO 3 / 2 A copolymer consisting of (CH3)2HSiO units. 1 / 2 Units and (CH3)(CF3C2H4)SiO Units and (CH3)2SiO Units and (CF3C2H4)SiO 3 / 2 and copolymers consisting of a unit.
[0061] The organohydrogenpolysiloxane of the component (D) may use either a single compound, or a combination of two or more different compounds.
[0062] This organohydrogenpolysiloxane is synthesized by a conventional method.
[0063] Here, component (D) has two hydrogen atoms (SiH groups) bonded to silicon atoms in one molecule, and is different from component (B) in that it has at least three hydrogen atoms bonded to silicon atoms in one molecule. Component (B) is also used as a surface treatment agent for component (C), whereas component (D) reacts with the alkenyl group in component (A) and is used as a crosslinking agent to obtain a cured product. That is, component (D) has two SiH groups, so if even one of them is deactivated, three-dimensional crosslinking will not occur. For this reason, in the present invention, component (C) is surface-treated with the above-mentioned component (B) so that component (D) to be mixed in the second liquid does not deteriorate over time.
[0064] For this reason, the amount of component (D) used is an amount such that the number of silicon-bonded hydrogen atoms (SiH groups) in component (D) per alkenyl group in component (A) is 0.01 to 3, preferably 0.05 to 2, and more preferably 0.2 to 1.5. If the number of SiH groups in component (D) is less than 0.01 per alkenyl group in component (A), the silicone cured product may become too soft and a stable silicone cured product may not be obtained, whereas if the number of SiH groups in component (D) is more than 3 per alkenyl group in component (A), the silicone cured product may become too hard and brittle.
[0065] In the present invention, it is preferable that the ratio of the total number of SiH groups in the above-mentioned components (B) and (D) to the number of alkenyl groups in component (A) ((total number of SiH groups in components (B) and (D)) / (number of alkenyl groups in component (A))) is 0.11 to 5, that is, the total number of SiH groups in components (B) and (D) is 0.11 to 5, particularly 0.25 to 4, per alkenyl group in component (A). If the total number of SiH groups in components (B) and (D) is 0.11 or more per alkenyl group in component (A), a stable silicone cured product with appropriate viscosity can be obtained, and if the total number of SiH groups in components (B) and (D) is 5 or less per alkenyl group in component (A), the silicone cured product will not be too hard and will have a suitable strength.
[0066] [(E) component] The component (E) of the composition of the present invention is a platinum group metal catalyst, which is a catalyst that promotes the addition reaction between the alkenyl group in the component (A) and the hydrogen atoms bonded to the silicon atoms in the components (B) and (D). For example, chloroplatinic acid, alcohol-modified chloroplatinic acid, coordination compounds of chloroplatinic acid with olefins, aldehydes, vinylsiloxanes, or acetylene compounds, tetrakis(triphenylphosphine)palladium, chlorotris(triphenylphosphine)rhodium, etc. are used, but platinum catalysts are preferred, and most preferably coordination compounds of chloroplatinic acid and vinylsiloxane, such as platinum-divinyltetramethyldisiloxane complex, are used.
[0067] The amount of component (E) to be blended may be a catalytic amount, but is usually 1 to 200 ppm, preferably 2 to 100 ppm, calculated as the mass of platinum group metal relative to component (A). By keeping the amount of component (E) within this range, appropriate curing properties can be obtained. Component (E) is contained only in the first liquid, and is not contained in the second liquid.
[0068] [Component (F)] The component (F) of the composition of the present invention is a reaction inhibitor that inhibits the progress of the hydrosilylation reaction and extends the shelf life and pot life. The component (F) is an organopolysiloxane having 1 to 4 alkenyl groups and 4 or less D units in one molecule, and the molecular structure may be cyclic or linear. Note that the component (A), which is the base polymer of the composition of the present invention, may have an alkenyl group and a D unit in one molecule, but is a different component from the component (F).
[0069] There are no particular limitations on the component (F), so long as it is an organopolysiloxane having 1 to 4 alkenyl groups and 4 or less D units in one molecule. Examples of the component (F) include linear organopolysiloxanes such as 1,3-divinyltetramethyldisiloxane, and cyclic organopolysiloxanes such as 1,3,5-trivinyl-1,3,5-trimethylcyclotrisiloxane, but are not limited to these.
[0070] In general, it is known that linear or cyclic organopolysiloxanes having alkenyl groups in the molecule and D units can be ligands of platinum group metal complexes. For example, it is known that 1,3-divinyltetramethyldisiloxane can be a ligand of platinum complexes in coordination compounds of chloroplatinic acid and vinylsiloxanes such as the so-called Karstedt catalyst (U.S. Pat. No. 3,775,452). In this way, organopolysiloxanes having alkenyl groups and D units form metal complexes as ligands and have the effect of promoting hydrosilylation reactions. On the other hand, organopolysiloxanes having alkenyl groups and D units also have the effect of suppressing the progress of hydrosilylation reactions by coordinating with the central metal of the catalyst as a reaction inhibitor. In the present invention, the structure of the organopolysiloxane (the number of alkenyl groups and the number of D units per molecule) that has the opposite effect on the hydrosilylation reaction is limited, and the amount of platinum group metal catalyst (component (E)) is reduced, while the amount of component (F) is set to a predetermined amount relative to component (A). By skillfully combining and adjusting components (E) and (F) in this way, the present invention is able to significantly suppress oil bleeding during and after curing of the composition, even though it contains organopolysiloxanes that have the opposite effects described above.
[0071] As described above, linear or cyclic organopolysiloxanes having alkenyl groups and D units in one molecule have the functions of both promoting and inhibiting the progress of the hydrosilylation reaction, that is, the functions are in a trade-off relationship. In addition curable silicone compositions, optimal control of the progress of the hydrosilylation reaction is an important issue, but in the present invention, the progress of the hydrosilylation reaction is appropriately controlled by optimizing the amount of catalyst and the amount of reaction regulator while using an organopolysiloxane having a specific structure as a reaction regulator. Such technical features of the present invention have not been known until now.
[0072] The amount of component (F) blended, relative to 100 parts by mass of component (A), of less than 0.01 part by mass will not provide sufficient shelf life or pot life, while more than 1 part by mass will decrease curability. Therefore, the blend amount of component (F) is in the range of 0.01 to 1 part by mass, and preferably in the range of 0.1 to 0.8 parts by mass.
[0073] [(G) component] In the composition of the present invention, a silane coupling agent (G) can be used as necessary. By blending the component (G), the effect of lowering the viscosity of the first liquid and the second liquid can be obtained. Examples of the silane coupling agent (G) include vinyl-based silane coupling agents, epoxy-based silane coupling agents, acrylic-based silane coupling agents, and long-chain alkyl-based silane coupling agents, and the like, and one type can be used alone or two or more types can be used in appropriate combination. Among them, long-chain alkyl-based silane coupling agents are preferred, and decyltrimethoxysilane is preferred.
[0074] In the present invention, when the component (G) is used, it is preferable to prepare a heat-treated mixture at a temperature of 70°C or higher using the above-mentioned component (C) alone or with multiple components including the component (C), but the component (C) can also be pretreated with the component (G). In this case, the pretreatment (surface treatment) method of the component (C) with the component (G) can be a spray method using a fluid nozzle, a stirring method with shear force, a dry method using a ball mill or mixer, or a wet method using a water-based or organic solvent-based system. The stirring is performed to a degree that does not cause destruction of the spherical aluminum oxide powder. In the dry method, the temperature in the system or the drying temperature after treatment is appropriately determined depending on the type of the surface treatment agent within a range in which the surface treatment agent does not volatilize or decompose, but is 80 to 180°C.
[0075] When component (G) is used, the amount used is preferably 0.1 to 5 parts by mass, and more preferably 1 to 5 parts by mass, per 100 parts by mass of the total of components (C). If it is 0.1 part by mass or more, a sufficient viscosity-lowering effect can be obtained, and if it is 5 parts by mass or less, an effect appropriate to the amount used can be obtained.
[0076] When component (G) is used, it can be used in both the first liquid and the second liquid. The ratio of component (G) used in the first liquid and the second liquid is not particularly limited, but for example, it can be blended in equal amounts in the first liquid and the second liquid.
[0077] [(H) component] The composition of the present invention may optionally use (H) an organopolysiloxane having at least one hydrolyzable silyl group represented by the following general formula (4) per molecule and having a viscosity of 0.01 to 30 Pa s at 25° C. The incorporation of component (H) has the effect of lowering the viscosity of the first and second liquids. [ka] (In the formula, R 4 are independently unsubstituted or substituted monovalent hydrocarbon groups; R 5 are independently an alkyl group, an alkoxyalkyl group, an alkenyl group or an acyl group, g is an integer of 5 to 100, and h is an integer of 1 to 3.
[0078] In the above formula (4), R 4are independently unsubstituted or substituted monovalent hydrocarbon groups having preferably 1 to 10 carbon atoms, more preferably 1 to 6 carbon atoms, and even more preferably 1 to 3 carbon atoms, examples of which include linear alkyl groups, branched alkyl groups, cyclic alkyl groups, alkenyl groups, aryl groups, aralkyl groups, and halogenated alkyl groups. Examples of linear alkyl groups include methyl groups, ethyl groups, propyl groups, hexyl groups, octyl groups, and decyl groups. Examples of branched alkyl groups include isopropyl groups, sec-butyl groups, isobutyl groups, tert-butyl groups, and 2-ethylhexyl groups. Examples of cyclic alkyl groups include cyclopentyl groups and cyclohexyl groups. Examples of alkenyl groups include vinyl groups and allyl groups. Examples of aryl groups include phenyl groups and tolyl groups. Examples of aralkyl groups include 2-phenylethyl groups and 2-methyl-2-phenylethyl groups. Examples of halogenated alkyl groups include a 3,3,3-trifluoropropyl group, a 2-(nonafluorobutyl)ethyl group, and a 2-(heptadecafluorooctyl)ethyl group. 4 As the alkyl group, a methyl group and a phenyl group are preferable.
[0079] In the above formula (4), R 5 are independently an alkyl group, an alkoxyalkyl group, an alkenyl group, or an acyl group. Examples of the alkyl group include R 4 Examples of the alkoxyalkyl group include the same straight chain alkyl group, branched chain alkyl group, and cyclic alkyl group as those exemplified in R. Examples of the alkoxyalkyl group include a methoxyethyl group, a methoxypropyl group, and the like, and preferably those having 2 to 10 carbon atoms. Examples of the alkenyl group include the same groups as those exemplified in the above R, and preferably those having 1 to 8 carbon atoms. Examples of the acyl group include an acetyl group, an octanoyl group, and the like, and preferably those having 2 to 10 carbon atoms. R 5 is preferably an alkyl group, and particularly preferably a methyl group or an ethyl group.
[0080] Furthermore, g is an integer of 5 to 100, and preferably an integer of 8 to 50;
[0081] Specific examples of suitable organopolysiloxanes of component (H) include the following: [ka] (In the formula, Me is a methyl group. The same applies hereinafter.)
[0082] The viscosity of the organopolysiloxane of component (H) at 25°C is typically 0.01 to 30 Pa·s, and preferably 0.01 to 10 Pa·s. If the viscosity is 0.01 Pa·s or more, oil bleeding of component (H) from the silicone composition does not occur. If the viscosity is 30 Pa·s or less, the resulting silicone composition has sufficient fluidity and provides good application workability.
[0083] When component (H) is used, the blending amount is preferably 5 to 900 parts by mass, more preferably 10 to 900 parts by mass, and even more preferably 15 to 700 parts by mass, per 100 parts by mass of component (A). When the blending amount of component (H) is 5 parts by mass or more, the effect of sufficiently lowering the viscosity is obtained, and when it is 900 parts by mass or less, oil bleeding of component (H) from the silicone composition does not occur.
[0084] When component (H) is used, it can be used in either or both of the first and second liquids. The ratio of component (H) used in the first and second liquids is not particularly limited, but for example, it can be blended in equal amounts in the first and second liquids.
[0085] In addition, when the (H) component is blended, it is preferable that the (H) component is blended together with the above-mentioned (A), (C) component, or (A) to (C) components, heat-treated at a temperature of 70°C or higher, and cooled to obtain a heat-treated mixture, after which the (E), (F) or (D) component is blended.
[0086] [Other ingredients] In addition to the above-mentioned components (A) to (H) as other compounding agents, the composition of the present invention may contain various known additives as necessary. For example, a cation exchange and / or amphoteric ion exchange type ion trapping agent that imparts an effect of improving the storage stability of the composition, an adhesion improver, a heat resistance improver, a colorant, etc. may be blended. The amount of each of these to be added is preferably 0.01 to 100,000 ppm by mass per the present composition.
[0087] [Production of a thermally conductive two-part addition-curable silicone composition] The composition of the present invention is a thermally conductive two-liquid addition curable silicone composition consisting of a first liquid and a second liquid, which contain the above components (A) to (F), and optionally the above components (G) and (H) and other components. The preparation of the first liquid and the second liquid will be explained below, but these are merely examples and are not intended to be limiting.
[0088] [1st liquid] The first liquid can be prepared by mixing a heat-treated mixture of components (A) and (C), and optionally components (G) and (H), so as to contain component (E) but not components (B), (D), and (F).
[0089] The heat-treated mixture is prepared by mixing the above-mentioned components (A) and (C), and if necessary, the components (G) and (H), for example, at 70°C or higher, preferably 100 to 200°C, more preferably 100 to 170°C, even more preferably 100 to 160°C, and particularly preferably 100 to 150°C, for preferably 60 minutes or more. There is no particular upper limit to the heat treatment time, but the heat treatment is preferably performed for 60 to 240 minutes, more preferably 60 to 180 minutes, and particularly preferably 60 to 120 minutes. If the heat treatment temperature is 70°C or higher, the surface treatment of the component (C) by the component (A) is sufficient. If the heat treatment temperature is 200°C or lower, there is no risk of the components (A), (G), and (H) decomposing. In addition, if the heat treatment time is sufficiently long, the surface treatment of the component (C) by the component (A) is sufficient.
[0090] The heat-treated mixture is prepared by mixing the above-obtained components (A) and (C), and optionally components (G) and (H), and heating the mixture at a predetermined temperature. The mixture is then cooled to preferably 0 to 50° C., more preferably room temperature (1 to 25° C.), and the above-mentioned component (E) is added thereto and mixed uniformly. Here, the heat-treated mixture and component (E) are mixed at room temperature (1 to 25° C.) for about 5 to 30 minutes, and the first liquid can be obtained by the above-mentioned method.
[0091] [Second liquid] The second liquid can be prepared by mixing a heat-treated mixture of components (A), (B), and (C), and optionally components (G) and (H), with components (D) and (F), and optionally other additives, but not containing component (E).
[0092] The heat-treated mixture is prepared by mixing the above components (A), (B), (C), and, if necessary, components (G) and (H) under heating at, for example, 70°C or higher, preferably 100 to 200°C, more preferably 100 to 170°C, even more preferably 100 to 160°C, and particularly preferably 100 to 150°C, for preferably 60 minutes or more. There is no particular upper limit to the heat treatment time, but the heat treatment is preferably performed for 60 to 240 minutes, more preferably 60 to 180 minutes, and particularly preferably 60 to 120 minutes. If the heat treatment temperature is 70°C or higher, the reaction between the hydrogen atoms bonded to the silicon atoms in component (B) and the reactive groups or reactive substances that may reduce the storage stability, such as Al-OH groups and residual inorganic acids in component (C), proceeds smoothly. If the heat treatment temperature is 200°C or lower, there is no risk of deterioration of the polymers themselves, components (A) and (B). Furthermore, if the heat treatment time is sufficiently long, the reaction between the hydrogen atoms bonded to silicon atoms in component (B) and reactive groups such as Al-OH groups in component (C) or reactive groups or reactive substances that reduce storage stability, such as residual inorganic acids, will proceed sufficiently, resulting in a sufficient improvement in storage stability.
[0093] The heat-treated mixture obtained by mixing the above-obtained components (A), (B), (C), and optionally components (G) and (H) and heating at a predetermined temperature is cooled to preferably 0 to 50°C, more preferably room temperature (1 to 25°C), and the above-mentioned components (D) and (F), and optionally other additives, are added and mixed uniformly. Here, the heat-treated mixture, components (D) and (F), and optionally other additives are mixed at room temperature (1 to 25°C) for about 5 to 30 minutes, and the second liquid can be obtained by the above-mentioned method.
[0094] As a mixing device for preparing the first and second liquids, a known mixer such as a static mixer, a planetary mixer, or a paddle mixer can be used.
[0095] In the composition of the present invention, the thermal conductivity of each of the first and second liquids is 2.0 to 7.0 W / m·K, preferably 2.2 to 7.0 W / m·K, in the hot disk method according to ISO 22007-2. If the thermal conductivity is too low, the heat dissipation performance of heat-generating electronic components may be insufficient. The thermal conductivity may be measured, for example, by measuring the thermal conductivity of the silicone composition before curing in a 25°C environment using a hot disk method thermal property measuring device TPS-2500S manufactured by Kyoto Electronics Manufacturing Co., Ltd. In order to set the thermal conductivity within the above range in the present invention, it can be achieved by setting the blending amount of the (C) component within the range specified above.
[0096] In the composition of the present invention, the viscosity of the first and second liquids at 25°C is 30 to 800 Pa·s, and preferably 30 to 700 Pa·s, respectively, when measured with a spiral viscometer (for example, a Malcom rotational viscometer (Type PC-10AA)) using rotor A at a rotation speed of 10 rpm (shear rate of 6 (1 / sec)). If the viscosity is too low, the shape retention of the composition may be insufficient, and if the viscosity is too high, workability may be difficult. In the present invention, the viscosity can be adjusted to be within the above range by adjusting the blending amount of component (C) within the range specified above.
[0097] In the composition of the present invention, if the difference in viscosity between the first and second liquids is small, they can be mixed uniformly using a static mixer such as a static mixer. In this case, when measuring with a spiral viscometer using rotor A at a rotation speed of 10 rpm (shear rate of 6 (1 / sec)), it is preferable that the difference in initial (preparation) viscosity between the first and second liquids is ±0 to 80%, particularly ±0 to 50%, based on the viscosity of the first liquid at 25°C.
[0098] In the composition of the present invention, it is preferable that the mixing ratio of the first liquid and the second liquid is approximately the same by mass. Specifically, it is desirable that the first liquid and the second liquid are mixed in a mass ratio of about 1:0.5 to 1:2, particularly 1:0.75 to 1:1.25, further 1:0.9 to 1:1.1, and especially 1:0.95 to 1:1.05.
[0099] In the composition of the present invention, the mixing device for the first liquid and the second liquid is not limited to a stationary mixer such as a static mixer, but may be a known mixer such as a planetary mixer or a paddle mixer.
[0100] The curing conditions of the composition of the present invention are not particularly limited, and may be the same as those of known addition reaction curing silicone compositions. For example, the composition can be sufficiently cured at room temperature, but may be heated if necessary. When heated, the curing conditions may be 40 to 180°C for 1 to 60 minutes.
[0101] The resulting cured product of the composition of the present invention preferably has a Shore OO hardness in the range of 5 to 95, particularly 10 to 90, as specified in ASTM D 2240-05.
[0102] (A) to (H) and other compounding ingredients can be added and mixed as described above.
[0103] [Characteristics of thermally conductive two-component addition-curable silicone compositions] The composition of the present invention preferably has the following properties:
[0104] (tack-free) When the first and second liquids produced according to the above composition are mixed in a mass ratio of 1:1 and a tack-free test is carried out at room temperature (25°C) according to JIS K6249, it is preferable that the thermally conductive two-liquid addition curing silicone composition has a tack-free time of 30 minutes or more and 200 minutes or less. If the tack-free time is 30 minutes or more, there is a sufficient time until the composition starts to harden, and workability is improved, and if it is 200 minutes or less, oil bleeding of the composition is suppressed, and there is no risk of contamination of surrounding members or deterioration of thermal performance. It is preferably 50 minutes or more and 180 minutes or less, and more preferably 60 minutes or more and 120 minutes or less.
[0105] (Oil bleed suppression) In the thermally conductive two-part addition curable silicone composition of the present invention, the spread (width) of oil bleed is preferably within the following range. (1) The first liquid and the second liquid produced according to the above composition are mixed in a mass ratio of 1:1, and 0.1 g of the mixture is applied to a ground glass having a surface roughness of 3 to 20 μm in arithmetic mean height and 10 to 100 μm in maximum height as specified in ISO 25178 so as to have a diameter of 3 to 5 mm. After leaving the mixture at 25°C for 24 hours, the width of oil bleed around the mixture is 1.0 mm or less. (2) The first and second liquids produced according to the above composition are mixed in a mass ratio of 1:1, and 0.1 g of the mixture is applied to a ground glass having a surface roughness of 3 to 20 μm in arithmetic mean height and 10 to 100 μm in maximum height as specified in ISO 25178 so as to have a diameter of 3 to 5 mm. After leaving the mixture at 150°C for 500 hours, the width of oil bleed around the mixture is 1.0 mm or less. (3) The first liquid and the second liquid produced according to the above composition are mixed in a mass ratio of 1:1, and 0.1 g of the mixture is applied to a ground glass having a surface roughness of 3 to 20 μm in arithmetic mean height and 10 to 100 μm in maximum height as specified in ISO 25178 so as to give a diameter of 3 to 5 mm. After leaving the mixture at 85°C and a humidity of 85% for 500 hours, the width of oil bleed around the mixture becomes 1.0 mm or less.
[0106] Such a composition of the present invention is preferable because there is sufficient time until the composition begins to harden, which results in good workability and suppression of oil bleeding, thereby eliminating the risk of contamination of surrounding components and deterioration of thermal performance. EXAMPLES
[0107] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0108] [Examples 1-6, Comparative Examples 1-5] First, prepare the following ingredients:
[0109] Component (A) A-1: Dimethylpolysiloxane terminated at both ends with dimethylvinylsiloxy groups, with a viscosity of 600 mPa·s at 25°C
[0110] (B) Component B-1: Trimethylsiloxy-blocked methylhydrogen-dimethylpolysiloxane represented by the following general formula (5) and having a viscosity of 28 mPa·s at 25°C. [ka]
[0111] (C) Component C-1: Aluminum oxide powder was heated and extracted with pure water at 120℃ for 48 hours, and the aqueous layer was measured by ion chromatography. + Fused spherical aluminum oxide powder with an ion content of 57 ppm and an average particle size of 43 μm C-2: Aluminum oxide powder was heated and extracted with pure water at 120℃ for 48 hours, and the aqueous layer was measured by ion chromatography. + Crushed aluminum oxide powder with an ion content of 11 ppm and an average particle size of 1.2 μm
[0112] (D) Component D-1: A dimethylhydrogensiloxy-blocked dimethylpolysiloxane represented by the following general formula (6) and having a viscosity of 17 mPa·s at 25°C. [ka]
[0113] (E) Component E-1: Platinum-divinyltetramethyldisiloxane complex having a platinum concentration of 1% by mass
[0114] Ingredient (F) F-1: 1,3-divinyltetramethyldisiloxane F-2: 1,3,5-trivinyl-1,3,5-trimethylcyclotrisiloxane F-3: 2,4,6,8,10-pentaethenyl-2,4,6,8,10-pentamethylcyclodecane pentasiloxane
[0115] (H) Component H-1: Organopolysiloxane represented by the following general formula (7) and having a viscosity of 30 mPa·s at 25°C. [ka]
[0116] The above components (A) to (H) were mixed as follows to obtain the thermally conductive two-component curing silicone compositions of Examples 1 to 6 and Comparative Examples 1 to 5. That is, components (A), (C), and (H) were added to a 5-liter planetary mixer (manufactured by Inoue Seisakusho Co., Ltd.), mixed at 150°C for 60 minutes, cooled to room temperature, and then component (E) was added and mixed for 20 minutes to obtain a first liquid. Next, components (A), (B), (C), and (H) were added to a 5-liter planetary mixer (manufactured by Inoue Seisakusho Co., Ltd.), mixed at 150°C for 60 minutes, and components (D) and (F) were added and mixed for 20 minutes to obtain a second liquid.
[0117] The properties of the resulting compositions were evaluated by the following methods, and the results are shown in Tables 1 and 2.
[0118] Viscosity: The viscosity was measured at 25° C. using a spiral viscometer (Malcom rotational viscometer, rotation speed: 10 rpm).
[0119] Thermal conductivity: The thermal conductivity of the composition before curing at 25° C. was measured using a thermal property measuring device TPS-2500S manufactured by Kyoto Electronics Manufacturing Co., Ltd. by the hot disk method in accordance with ISO 22007-2.
[0120] Tack-free time: A tack-free test was performed at room temperature (25°C) according to JIS K6249. If the tack-free time is shorter than 30 minutes, the composition may begin to cure too quickly, resulting in a significant decrease in workability, whereas if it is longer than 200 minutes, the oil bleeding of the composition may worsen, resulting in contamination of surrounding materials and deterioration of thermal performance.
[0121] Oil-bleed test-1: The first and second liquids manufactured according to the above composition were mixed in a 1:1 ratio, and 0.1 g of the mixture was applied to a ground glass having a surface roughness of 3 to 20 μm in arithmetic mean height and 10 to 100 μm in maximum height as specified in ISO 25178, so that the diameter was 3 to 5 mm. After leaving it at room temperature (25°C) for 24 hours, the spread of oil-bleed around the mixture (unit: mm) was measured.
[0122] Oil-bleed test-2: The first and second liquids manufactured according to the above composition were mixed in a 1:1 ratio, and 0.1 g of the mixture was applied to a ground glass having a surface roughness of 3 to 20 μm in arithmetic mean height and 10 to 100 μm in maximum height as specified in ISO 25178, so that the diameter was 3 to 5 mm. After leaving the mixture in a chamber at 150°C for 500 hours, the spread of oil-bleed around the mixture (unit: mm) was measured.
[0123] Oil-bleed test-3: The first and second liquids manufactured according to the above composition were mixed in a 1:1 ratio, and 0.1 g of the mixture was applied to a ground glass having a surface roughness of 3 to 20 μm in arithmetic mean height and 10 to 100 μm in maximum height as specified in ISO 25178, so that the diameter was 3 to 5 mm. After leaving the mixture in a chamber at 85°C and 85% humidity for 500 hours, the spread of oil-bleed around the mixture (unit: mm) was measured.
[0124] The measurement methods for the Oil Bleed Tests 1 to 3 in (4), (5), and (6) above will be explained with reference to FIG. 1. Mixture 2 (thermally conductive two-component addition-curable heat-dissipating silicone composition) prepared by mixing the first and second components in a 1:1 mass ratio, each prepared in the amounts shown in Tables 1 and 2, was applied in an amount of 0.1 g to a diameter of 3 to 5 mm on frosted glass 1 (exhibiting a surface roughness of arithmetic mean height of 3 to 20 μm and maximum height of 10 to 100 μm as specified in ISO 25178). After leaving the glass under the above-mentioned specified conditions, the average value of the spread (width) from the periphery of mixture 2 in the oil-bleeded portion (oil-bleed portion 3), i.e., the spread d (unit: mm) of the oil bleed, was measured.
[0125] [Table 1]
[0126] [Table 2]
[0127] The results in Tables 1 and 2 demonstrate that the thermally conductive silicone compositions of Examples 1 to 6, which satisfy the requirements of the present invention, are thermally conductive and exhibit little or no oil bleeding even when exposed to room temperature (25°C) or high temperature and humidity conditions during and after curing of the composition.
[0128] On the other hand, in Comparative Example 1, no reaction inhibitor (F) was added and only a very small amount of catalyst ligand was used, which led to an earlier start of curing and a shorter tack-free time. In other words, although divinyltetramethyldisiloxane also acts as a reaction inhibitor, the amount present in the system as a ligand in the hydrosilylation catalyst is insufficient to meet the amount required for component (F), and a sufficient time cannot be ensured until the composition starts to cure.
[0129] In Comparative Example 2, the amount of reaction inhibitor (F) added was large, which delayed the curing start time, lengthened the tack-free time, and confirmed significant bleeding of 1.0 mm or more during the oil-bleed test.
[0130] In Comparative Example 3, the amount of component (C) added was too small, so the thermal conductivity was below 2.0 W / m·K and sufficient thermal conductivity could not be ensured.
[0131] In Comparative Example 4, the amount of component (C) added was too large, so that the viscosity increased significantly and the mixture did not become grease (paste-like) but became lumpy.
[0132] In Comparative Example 5, 2,4,6,8,10-pentaethenyl-2,4,6,8,10-pentamethylcyclodecane pentasiloxane (F-3) was added as a reaction inhibitor for component (F), which resulted in excessive suppression of the hydrosilylation reaction, resulting in a significant extension of the tack-free time and significant bleeding during the oil-bleed test. That is, F-1 and F-2 used in the examples are organopolysiloxanes having 1 to 4 alkenyl groups and 4 or less D units in one molecule and satisfy the requirements of component (F) of the present invention, whereas F-3, which is a cyclic organopolysiloxane having 5 alkenyl groups and 5 D units in one molecule, does not satisfy the requirements of component (F) above, resulting in the above-mentioned problems.
[0133] The present specification includes the following aspects. [1]: A thermally conductive two-component addition curable silicone composition, (A) The following average composition formula (1) R a R 1 b SiO (4-a-b) / 2 (1) (wherein R is independently an alkenyl group; R 1 are independently an unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bond, a is 0.0001 to 0.2, b is 1.7 to 2.2, and a+b is a positive number satisfying 1.9 to 2.4. and having at least two alkenyl groups bonded to silicon atoms in one molecule, (C) Aluminum oxide powder was heated and extracted with pure water at 120℃ for 48 hours, and the aqueous layer was measured for Na by ion chromatography. + Aluminum oxide powder with an ionic content of 100 ppm or less, and (E) Platinum group metal catalyst: 1 to 200 ppm by mass of platinum group metal relative to component (A) A first liquid containing (A) The following average composition formula (1) R a R 1 b SiO (4-a-b) / 2 (1) (wherein R is independently an alkenyl group; R 1 are independently an unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bond, a is 0.0001 to 0.2, b is 1.7 to 2.2, and a+b is a positive number satisfying 1.9 to 2.4. and having at least two alkenyl groups bonded to silicon atoms in one molecule, (B) The following average composition formula (2) R 2 c H d SiO (4-c-d) / 2 (2) (In the formula, R 2 are independently an unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bond, c is 0.7 to 2.2, d is 0.001 to 0.5, and c+d is a positive number that satisfies 0.8 to 2.5. an organohydrogenpolysiloxane having at least three hydrogen atoms bonded to silicon atoms in one molecule, wherein the number of silicon-bonded hydrogen atoms (SiH groups) in component (B) is 0.1 to 2 per alkenyl group in component (A); (C) Aluminum oxide powder was heated and extracted with pure water at 120℃ for 48 hours, and the aqueous layer was measured for Na by ion chromatography. + Aluminum oxide powder with an ion content of 100 ppm or less, (D) The average composition formula (3) below R 3 e H f SiO (4-e-f) / 2 (3) (In the formula, R 3 are independently an unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bonds, e is a positive number that satisfies 0.7 to 2.2, f is a positive number that satisfies 0.001 to 0.5, and e+f is a positive number that satisfies 0.8 to 2.5. an organohydrogenpolysiloxane different from component (B) having two hydrogen atoms bonded to silicon atoms in one molecule: component (D) in an amount such that there are 0.01 to 3 silicon-bonded hydrogen atoms (SiH groups) per alkenyl group in component (A), and (F) Reaction control agent: A reaction control agent having 1 to 4 alkenyl groups in one molecule and a D unit (R 4 2SiO 2 / 2 )(R 4 are independently unsubstituted or substituted monovalent hydrocarbon groups that do not have aliphatic unsaturated bonds. and a second liquid comprising the composition, a thermally conductive two-part addition curable silicone composition, wherein the first part does not contain the components (B), (D), or (F), the second part does not contain the component (E), the total amount of the component (A) in the composition is 100 parts by mass, the total amount of the component (C) is 1,000 to 7,000 parts by mass, and the amount of the component (F) is 0.01 to 1 part by mass, the first part and the second part each have a thermal conductivity of 2.0 to 7.0 W / m K when measured using a hot disk method in accordance with ISO 22007-2, and the first part and the second part each have a viscosity at 25°C of 30 to 800 Pa s when measured using a spiral viscometer with rotor A at a rotation speed of 10 rpm (shear rate of 6 (1 / sec)). [2]: The thermally conductive two-component addition curable silicone composition according to [1], wherein the ratio of the total number of SiH groups in component (B) and component (D) to the number of alkenyl groups in component (A) is 0.11 to 5. [3]: Furthermore, a silane coupling agent (G) and / or a compound represented by the following general formula (4) [ka] (In the formula, R 4 are independently unsubstituted or substituted monovalent hydrocarbon groups; R 5 are independently an alkyl group, an alkoxyalkyl group, an alkenyl group or an acyl group, g is an integer of 5 to 100, and h is an integer of 1 to 3. and wherein the first liquid and / or the second liquid contain an organopolysiloxane (H) having a viscosity of 0.01 to 30 Pa s at 25°C. [4]: A thermally conductive two-component addition-curable silicone composition according to any one of [1] to [3], characterized in that when the first liquid and the second liquid are mixed in a 1:1 mass ratio and a tack-free test is carried out at 25°C in accordance with JIS K6249, the tack-free time is 30 minutes or more and 200 minutes or less. [5]: A thermally conductive two-component addition curable silicone composition according to any one of [1] to [4], characterized in that a mixture obtained by mixing the first liquid and the second liquid in a mass ratio of 1:1 is applied to a ground glass surface having a surface roughness of 3 to 20 μm in arithmetic mean height and 10 to 100 μm in maximum height as specified in ISO 25178 in an amount of 0.1 g to a diameter of 3 to 5 mm, and the mixture is left at 25°C for 24 hours, after which the width of oil bleed around the mixture is 1.0 mm or less. [6]: A thermally conductive two-component addition-curable silicone composition according to any one of [1] to [5], characterized in that a mixture obtained by mixing the first liquid and the second liquid in a mass ratio of 1:1 is applied to a ground glass surface having a surface roughness of 3 to 20 μm in arithmetic mean height and 10 to 100 μm in maximum height as specified in ISO 25178 in an amount of 0.1 g to a diameter of 3 to 5 mm, and the mixture is left at 150°C for 500 hours, after which the width of oil bleed around the mixture is 1.0 mm or less. [7]: A thermally conductive two-component addition-curable silicone composition according to any one of [1] to [6], characterized in that a mixture obtained by mixing the first liquid and the second liquid in a mass ratio of 1:1 is applied to a ground glass surface having a surface roughness of 3 to 20 μm in arithmetic mean height and 10 to 100 μm in maximum height as specified in ISO 25178 in an amount of 0.1 g to a diameter of 3 to 5 mm, and the mixture is left at 85°C and a humidity of 85% for 500 hours, after which the width of oil bleed around the mixture is 1.0 mm or less.
[0134] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention. [Explanation of symbols]
[0135] 1... ground glass, 2... thermally conductive two-component addition curing type heat dissipating silicone composition (mixture), 3...Oil bleed section, d...Oil bleed spread (mm).
Claims
1. A thermally conductive two-part addition curable silicone composition, comprising: (A) The following average composition formula (1) R a R 1 b SiO (4-a-b)/2 (1) (Wherein, R is independently an alkenyl group; R 1 are independently an unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bonds, a is 0.0001 to 0.2, b is 1.7 to 2.2, and a+b is a positive number satisfying 1.9 to 2.
4. and having at least two alkenyl groups bonded to silicon atoms in one molecule, (C) Aluminum oxide powder was heated and extracted with pure water at 120°C for 48 hours, and the aqueous layer was measured by ion chromatography. + Aluminum oxide powder having an ion amount of 100 ppm or less, and (E) Platinum group metal catalyst: 1 to 200 ppm by mass of platinum group metal relative to component (A) A first liquid containing (A) The following average composition formula (1) R a R 1 b SiO (4-a-b)/2 (1) (Wherein, R is independently an alkenyl group; R 1 are independently an unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bonds, a is 0.0001 to 0.2, b is 1.7 to 2.2, and a+b is a positive number satisfying 1.9 to 2.
4. and having at least two alkenyl groups bonded to silicon atoms in one molecule, (B) The following average composition formula (2): R 2 c H d SiO (4-c-d)/2 (2) (In the formula, R 2 are independently an unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bonds, c is 0.7 to 2.2, d is 0.001 to 0.5, and c+d is a positive number that satisfies the range of 0.8 to 2.
5. and an organohydrogenpolysiloxane having at least three hydrogen atoms bonded to silicon atoms per molecule, wherein the amount of silicon-bonded hydrogen atoms (SiH groups) in component (B) is 0.1 to 2 per alkenyl group in component (A), (C) Aluminum oxide powder was heated and extracted with pure water at 120°C for 48 hours, and the aqueous layer was measured by ion chromatography. + Aluminum oxide powder having an ion amount of 100 ppm or less; (D) The following average composition formula (3): R 3 e H f SiO (4-e-f)/2 (3) (In the formula, R 3 are independently an unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bonds, e is a positive number that satisfies 0.7 to 2.2, f is a positive number that satisfies 0.001 to 0.5, and e+f is a positive number that satisfies 0.8 to 2.
5. an organohydrogenpolysiloxane different from component (B) having two hydrogen atoms bonded to silicon atoms in one molecule, in which the number of silicon-bonded hydrogen atoms (SiH groups) in component (D) is 0.01 to 3 per alkenyl group in component (A), and (F) Reaction control agent: a reaction control agent having 1 to 4 alkenyl groups in one molecule and a D unit (R 4 2 SiO 2/2 ) (R 4 are independently unsubstituted or substituted monovalent hydrocarbon groups that do not have aliphatic unsaturated bonds. and a second liquid comprising the composition, a thermally conductive two-part addition curable silicone composition, characterized in that the first liquid does not contain the components (B), (D), or (F), the second liquid does not contain the component (E), the total amount of the component (A) in the composition is 100 parts by mass, the total amount of the component (C) is 1,000 to 7,000 parts by mass, and the amount of the component (F) is 0.01 to 1 part by mass, the first liquid and the second liquid each have a thermal conductivity of 2.0 to 7.0 W / m K when measured using a hot disk method in accordance with ISO 22007-2, and the first liquid and the second liquid each have a viscosity at 25°C of 30 to 800 Pa s when measured using a spiral viscometer with rotor A at a rotation speed of 10 rpm (shear rate of 6 (1 / sec)).
2. The thermally conductive two-part addition curable silicone composition according to claim 1, characterized in that the ratio of the total number of SiH groups in component (B) and component (D) to the number of alkenyl groups in component (A) is 0.11 to 5.
3. Furthermore, a silane coupling agent (G) and / or a compound represented by the following general formula (4) 【Chemistry 1】 (In the formula, R 4 are independently unsubstituted or substituted monovalent hydrocarbon groups; R 5 are independently an alkyl group, an alkoxyalkyl group, an alkenyl group, or an acyl group, g is an integer of 5 to 100, and h is an integer of 1 to 3. and wherein the first liquid and / or the second liquid contain an organopolysiloxane (H) having a viscosity of 0.01 to 30 Pa s at 25° C. and a viscosity of 0.01 to 30 Pa s at 25° C.
4. 2. The thermally conductive two-component addition curable silicone composition according to claim 1, characterized in that when the first liquid and the second liquid are mixed in a mass ratio of 1:1 and a tack-free test is carried out at 25°C in accordance with JIS K6249, the tack-free time is 30 minutes or more and 200 minutes or less.
5. The thermally conductive two-component addition curable silicone composition according to claim 1, characterized in that a mixture obtained by mixing the first liquid and the second liquid in a 1:1 mass ratio is applied to a ground glass surface having a surface roughness of 3 to 20 μm in arithmetic mean height and 10 to 100 μm in maximum height as specified in ISO 25178 in an amount of 0.1 g to a diameter of 3 to 5 mm, and the mixture is left at 25° C. for 24 hours, after which the width of oil bleed around the mixture is 1.0 mm or less.
6. The thermally conductive two-component addition curable silicone composition according to claim 1, characterized in that a mixture obtained by mixing the first liquid and the second liquid in a 1:1 mass ratio is applied to a ground glass surface having a surface roughness of 3 to 20 μm in arithmetic mean height and 10 to 100 μm in maximum height as specified in ISO 25178 in an amount of 0.1 g to a diameter of 3 to 5 mm, and the mixture is left at 150° C. for 500 hours, after which the width of oil bleed around the mixture is 1.0 mm or less.
7. The thermally conductive two-component addition curable silicone composition according to claim 1, characterized in that a mixture obtained by mixing the first liquid and the second liquid in a 1:1 mass ratio is applied to a ground glass surface having a surface roughness of 3 to 20 μm in arithmetic mean height and 10 to 100 μm in maximum height as specified in ISO 25178 in an amount of 0.1 g to a diameter of 3 to 5 mm, and the mixture is left at 85°C and a humidity of 85% for 500 hours, after which the width of oil bleed around the mixture is 1.0 mm or less.
Citation Information
Patent Citations
Composition for heat radiation silicone gel and heat radiation silicone sheet obtained by curing the same
JP2008143980A
Silicone gel composition, method for producing silicone gel composition and silicone gel cured product
JP2020029535A
Heat-dissipating gel-type silicone rubber composition
JP2020512465A
Thermally conductive addition curing-type silicone composition and method for producing the same
JP2021187874A
Heat-conductive two-liquid addition reaction-curing type silicone composition, and method of producing the same
JP2022029985A